2007
DOI: 10.1007/s00436-007-0715-4
|View full text |Cite
|
Sign up to set email alerts
|

Surface fine topography and PCR-based determination of metacercaria of Paragonimus sp. from edible crabs in Arunachal Pradesh, Northeast India

Abstract: In several mountainous regions of Northeastern India, foci of Paragonimus infection reportedly involving species that are known to prevail in China have been identified. The present study was undertaken to demonstrate the surface fine topography and sequence analysis of the ribosomal deoxyribonucleic acid (rDNA; second internal transcribed spacer, ITS2) of the metacercarial stages of the lung fluke collected from a mountain stream of the area (Miao, Changlang District in Arunachal Pradesh). The encysted metace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 23 publications
1
27
0
Order By: Relevance
“…22,23 Prior studies have used molecular diagnostics to speciate Paragonimus metacerariae in snails. [24][25][26] However, relatively few studies have attempted to detect Paragonimus DNA in the definitive host. [27][28][29] Our PCR studies confirmed the presence of P. kellicotti DNA in clinical specimens from two Missouri cases.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Prior studies have used molecular diagnostics to speciate Paragonimus metacerariae in snails. [24][25][26] However, relatively few studies have attempted to detect Paragonimus DNA in the definitive host. [27][28][29] Our PCR studies confirmed the presence of P. kellicotti DNA in clinical specimens from two Missouri cases.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, they determined that the species present in this area was P. westermani. Once the species designation was fully established using molecular methods (i.e., once any doubt regarding species designation was removed), then the researchers were able to more fully characterize the microscopic morphology of this stage of this species (178). This is an example of how molecular methods may actually strengthen, rather than replace, traditional morphology-based parasitologic methods.…”
Section: Molecular Testingmentioning
confidence: 99%
“…With the help of these studies, 3 new genera (Caulanus gen. nov., Latuterus gen. nov., (Miller & Cribb, 2007) and Allobilharzia gen. nov. (Kolářová et al, 2006) and 49 new species have been established. Molecular studies of ITS rDNA region verifi ed as promising genetic marker having broad range of application for phylogenetic analyses at generic and species level (Blair et al, 1999;Iwagami et al, 2000;Huang et al, 2004;Tandon et al, 2007;). According to Vilas et al (2005) and Al-Kandari et al (2011) ITS-1 is more variable than ITS-2 due to variable nucleotide repeats (Warberg et al, 2005 in microphallid species) and accretion of substitutions at higher rate (Morgan & Blair, 1995;van Herwerden et al, 1999;Tkach et al, 2000).…”
Section: Resultsmentioning
confidence: 99%